Longitudinal Strength Analysis Considering the Cargo Load on Very Large Crude Carrier (VLCC) - Suci, Indah Melati; Sitepu, Ganding; Muis Alie, Muhammad Zubair (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
The ultimate strength of the Very Large Crude Carrier (VLCC) is an important aspect that must be analyzed. The purpose of this study was to analyze the ultimate strength of the VLCC ship in terms of deformation under hogging and sagging conditions on the deck and bottom. Deformation is a change in the shape or size of a material due to a workforce that is applied to you. In this case, the deformation in question arises due to the working moment. This deformation analysis was carried out using the Non-Linear Finite Element Analysis (NLFEA) method. This analysis is carried out by presenting the support or Multi-Point Constraints (MPC) in the cross-section, as well as moments of 6.52 × 1012  for hogging conditions and -5.5 × 1012  for slack conditions.